(untitled) (International Conference on Computers in Education, 2020)
Outdoor spaces often have positive connotations for its ability to enhance learning. However, there is a chance that this learning environment unable to provide the expected learning outcomes. This paper explores whether and to what extent the practice of learning in this environment is consistent or conflicting with John Dewey’s concept of continuity of experience. Critical reflection was made on two residential outdoor environmental education courses to observe how residential outdoor learning environments courses are exposed to the risk of learning discontinuity. As a result, the study reveals that there is in fact a risk of learning discontinuity when the learning that take place in outdoor environments adopt a threefold relationship between unfamiliarity, contrast and spatial movement. The implication of this paper is the suggestion to find a way to connect and reconnect the learning environments involved in learning